2012
DOI: 10.1016/j.cardfail.2012.01.014
|View full text |Cite
|
Sign up to set email alerts
|

Dyads Affected by Chronic Heart Failure: A Randomized Study Evaluating Effects of Education and Psychosocial Support to Patients With Heart Failure and Their Partners

Abstract: Background Chronic heart failure (CHF) causes great suffering for both patients and their partners. The aim of this study was to evaluate the effects of an integrated dyad care program with education and psychosocial support to patients with CHF and their partners during a postdischarge period after acute deterioration of CHF. Methods One hundred fifty-five patient-caregiver dyads were randomized to usual care (n = 71) or a psychoeducation intervention (n = 84) delivered in 3 modules through nurse-led face-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
189
1
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 133 publications
(203 citation statements)
references
References 36 publications
4
189
1
6
Order By: Relevance
“…However, there was great heterogeneity and incompleteness in reporting both the number of sessions and time spent per session precluding an accurate description of dose and strength of dose for some interventions. As an example of this heterogeneity, Ågren et al (Agren et al, 2012) reported an intervention comprised of three components (face-to-face counseling, computer-based program and written materials). The intervention involved three sessions of 60 minutes each suggesting 180 minutes of direct contact with an interventionist during the intervention.…”
Section: Component Numbers the Number Of Individual Components Per Imentioning
confidence: 99%
See 4 more Smart Citations
“…However, there was great heterogeneity and incompleteness in reporting both the number of sessions and time spent per session precluding an accurate description of dose and strength of dose for some interventions. As an example of this heterogeneity, Ågren et al (Agren et al, 2012) reported an intervention comprised of three components (face-to-face counseling, computer-based program and written materials). The intervention involved three sessions of 60 minutes each suggesting 180 minutes of direct contact with an interventionist during the intervention.…”
Section: Component Numbers the Number Of Individual Components Per Imentioning
confidence: 99%
“…Countries where interventions were tested included the United States, (Bull et al, 2000;Dunbar et al, 2005;Dunbar et al, 2013;Piamjariyakul et al, 2015;Piette et al, 2008;Piette et al, 2015) Sweden, (Ågren et al, 2015;Agren et al, 2012) New Zealand, (Kenealy et al, 2015) Iran, (Hasanpour-Dehkordi et al, 2016) and Thailand. (Srisuk et al, 2015) Settings where the intervention was initiated or where the majority of the interventions were delivered included hospitals, (Agren et al, 2012;Bull et al, 2000;Hasanpour-Dehkordi et al, 2016;Kenealy et al, 2015;Piette et al, 2008;Schwarz et al, 2008) clinics, (Ågren et al, 2015;Agren et al, 2012;Dunbar et al, 2013;Piamjariyakul et al, 2015;Srisuk et al, 2015) home, (Agren et al, 2012) a U.S. Veterans Administration (clinic or hospital), (Piette et al, 2008;Piette et al, 2015) and in a clinical research center. (Dunbar et al, 2005) Two studies (Agren et al, 2012;Piette et al, 2008) included multiple sites to support the transition from hospital to home or increase recruitment.…”
Section: Dyadic Intervention Contextsmentioning
confidence: 99%
See 3 more Smart Citations